L´ELECTION PRESIDENTIELLE FRANCAISE - Ramonet, Ignacio (La Sociología en sus Escenarios, 2009)
Abstract. In the history of Ve République, the victory of Mr. Nicolas Sarkozy on May 6, 2007, with the second turn of the presidential election, with 53% of the voices, marks a turning. Because it is not a question of the simple French line renewal to the capacity - that it occupied on the most level of 1958 to 1981 and again since 1995-. The program of the candidate of the Union for a popular movement (UMP) and the forces which he wanted to gather around him mark a major inflecting: they make the first of it chair at the same time néolibéral, authoritative, pro-American and pro-Israeli. Resumen. En la historia de la República, la victoria de Sr. Nicolas Sarkozy el 6 de mayo de 2007, con la segunda vuelta de la elección presidencial, con el 53% de las voces, marca dar vuelta. Porque no es una cuestión de la línea francesa, la simple renovación a la capacidad que ocupó en la mayoría del nivel de 1958 a 1981 y otra vez desde 1995. El programa del candidato de la unión para un movimiento popular (UMP) y las fuerzas que él deseó para recolectar alrededor de él la marca un descenso del comandante: hacen de él, el primer, al mismo tiempo néolibéral, autoritaria, favorable-Americana y favorable-Israelí.